Postpartum Doula and Peer Telephone Support for Postpartum Depression - Dwenda Kay Gjerdingen; Patricia McGovern; Rebekah Pratt; Linda Johnson; Scott Crow (SAGE Publishing, 2013)
Objectives: This research provides the first test of feasibility of recruiting postpartum doulas and depressed mothers for a peer support intervention study and begins to evaluate the benefit of postpartum doula support and peer telephone support for at-risk mothers. Methods: The authors recruited postpartum doulas from national doula organizations, peer telephone supporters from nursing referrals, and mothers with depressive symptoms from 3 local hospitals, local medical practices, Web sites, and community organizations. Participating mothers were randomized to 3 groups-postpartum doula, peer telephone support, and control group. Surveys were completed at 0, 3, and 6 months postenrollment. Results: Thirty-nine mothers with depressive symptoms, 6 postpartum doulas, and 6 peer telephone supporters participated. The postpartum doula group, compared with the other 2 groups, had a higher proportion of women with a previous history of depression, and similarly, a higher proportion of women who were depressed and receiving depression treatment at the 6-month follow-up. Satisfaction with study-sponsored support was greater in the postpartum doula group than in the telephone support group. Conclusions: It is feasible to recruit postpartum doulas, peer telephone supporters, and mothers with depressive symptoms for a peer support intervention trial. Mothers were more satisfied with postpartum doulas than peer telephone support. The authors recommend further research to assess the benefit of postpartum doula support for postpartum depression as adjunctive or alternative therapy.